1989
DOI: 10.1007/bf00381466
|View full text |Cite
|
Sign up to set email alerts
|

Bright white light does not improve narcoleptic symptoms

Abstract: Bright white light (500lx) for 4 h/day was applied to seven narcoleptic patients (age 47-65 years, mean 55 years). The effects of the light on the disturbed sleep-wake cycle in narcoleptics were investigated by the measurement of the following parameters: (1) excessive daytime sleepiness and sustained attention (multiple sleep latency test); (2) rest-activity cycles; (3) self-ratings (mood, anxiety, tiredness); (4) urinary cycles of 6-OH melatonin sulphate and cortisol; (5) sleep EEG. Treatment with bright lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Indeed, previously we have shown that GABAergic mechanisms affect melatonin release (Kalsbeek et al, 1996(Kalsbeek et al, , 1999(Kalsbeek et al, , 2000. Several papers have delineated melatonin secretion in narcolepsy patients, primarily focusing on whether altered melatonin secretion could contribute to EDS and nocturnal sleep disturbances (Ahmed et al, 1991;Birau et al, 1982aBirau et al, , 1982bBlazejova et al, 2000Blazejova et al, , 2008Hajek et al, 1989). Although most of these studies found melatonin levels within the normal range in narcolepsy patients, in a more recent study Blazejova et al (2008) discovered elevated saliva melatonin levels during the day in almost half of the patients.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, previously we have shown that GABAergic mechanisms affect melatonin release (Kalsbeek et al, 1996(Kalsbeek et al, , 1999(Kalsbeek et al, , 2000. Several papers have delineated melatonin secretion in narcolepsy patients, primarily focusing on whether altered melatonin secretion could contribute to EDS and nocturnal sleep disturbances (Ahmed et al, 1991;Birau et al, 1982aBirau et al, , 1982bBlazejova et al, 2000Blazejova et al, , 2008Hajek et al, 1989). Although most of these studies found melatonin levels within the normal range in narcolepsy patients, in a more recent study Blazejova et al (2008) discovered elevated saliva melatonin levels during the day in almost half of the patients.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, others researchers (Stanley 2003, Sadeh 1995 have suggested that actigraphy is a potentially useful and cost-effective data collection tool that may be used to explore sleep-wake activity, monitor treatment processes and activity rhythms. To date, only a single study by Hajek et al(1989) has used actigraphy to assess treatment effects in narcolepsy patients. This study found that a small group of narcolepsy subjects exposed to bright light showed no improvement in either objectively or subjectively measured symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The actigraphic study of nocturnal sleep has seen the development of many different algorithms with various degrees of correlation with polysomnographic measures (Hajek et al, 1989). The study of diurnal functioning using actigraphs has had to adopt different measures.…”
mentioning
confidence: 99%
“…Several studies evaluating melatonin levels in patients with narcolepsy have demonstrated levels of melatonin similar to those found in non-narcoleptic individuals [ 176 ]. However, one study examining the pattern of melatonin secretion in narcolepsy with cataplexy found that though mean concentrations were similar to controls, there was a signifi cantly higher percentage of melatonin secreted during the day in those with narcolepsy [ 177 ].…”
Section: Melatonin and Hypersomniasmentioning
confidence: 94%